2014
DOI: 10.1039/c4ra08571j
|View full text |Cite
|
Sign up to set email alerts
|

GaN:Pr3+ nanostructures for red solid state light emission

Abstract: The photoluminescence of praseodymium implanted and annealed GaN films, quantum wells, nanowires and quantum dots was studied. After implantation and annealing, Pr 3+ intra-shell luminescence was achieved for all the analysed samples. In the trivalent charge state the ions' luminescence was found to be dominated by the red lines of the 3 P 0 / 3 F 2 transition. In the case of GaN films, an intense red emission is observed with the naked eye at room temperature. Photoluminescence excitation indicates that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Coexistence of Eu in 2+ and 3+ oxidation states has also been reported for Eu-doped ZnO nanowires63 . In contrast to GaN, in the case of ZnO substitutional Eu is expected to reside in the 2+ charge state but interaction with intrinsic defects allows the stabilization in the 3+64 ,65 .We observe that the Eu 2+ contribution decreases when the fluence is lowered to 5×1014 at/cm and becomes hardly visible for the HTHP annealed reference sample implanted to a fluence of 1×10 14 at/cm 2 , which shows an Eu 2+ fraction of only 16%. A low Eu 2+ fraction of 18% is also seen for NW samples implanted to a fluence as high as 1×1015 at/cm 2 provided they are implanted at 600°C.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Coexistence of Eu in 2+ and 3+ oxidation states has also been reported for Eu-doped ZnO nanowires63 . In contrast to GaN, in the case of ZnO substitutional Eu is expected to reside in the 2+ charge state but interaction with intrinsic defects allows the stabilization in the 3+64 ,65 .We observe that the Eu 2+ contribution decreases when the fluence is lowered to 5×1014 at/cm and becomes hardly visible for the HTHP annealed reference sample implanted to a fluence of 1×10 14 at/cm 2 , which shows an Eu 2+ fraction of only 16%. A low Eu 2+ fraction of 18% is also seen for NW samples implanted to a fluence as high as 1×1015 at/cm 2 provided they are implanted at 600°C.…”
mentioning
confidence: 68%
“…For the case of the doped thin films (Fig. 9b) the intensity first increases with the fluence up to 5×10 14 at/cm and then decreases again due to the severe lattice damage which could not be removed by thermal annealing. This behavior is similar to that observed previously for implantations performed along the c-axis.…”
Section: Optical Activationmentioning
confidence: 96%
See 1 more Smart Citation
“…18,22 This method is a key technology in the semiconductor industry and allows the introduction of dopants in a controlled way and without the limitations of the solubility of the dopant in the matrix. 23 Previous works from our group 9,24 revealed that it is possible to achieve optical activation of the RE ions in GaN NWs by ion implantation and postimplantation thermal annealing and showed that the emission of the doped NWs, in terms of intensity and thermal stability, is comparable with those obtained for GaN layers processed in similar conditions. 9,24 In the present work different GaN structures (layers and NWs) were doped with Eu 3+ by ion implantation.…”
Section: Introductionmentioning
confidence: 90%
“…Rare-earth (RE)-doped semiconductors have been widely investigated as a class of materials with promising properties, especially in the optoelectronic area, taking advantage of the remarkable atomic-like intra-4f n transitions of the trivalent charged RE ions. Gallium nitride (GaN) is a direct wide-bandgap semiconductor with a bandgap energy of 3.4 eV at room temperature . GaN and its ternary alloys are well-established materials in solid-state optics/lighting/optoelectronic applications such as light-emitting diodes (LEDs) and laser diodes (LDs). Among the main advantages as a host for RE ions, GaN exhibits a high transparency which makes it suitable for the incorporation of the ladder-like RE 3+ electronic energy levels promoting the ion optical activation with reduced luminescence thermal quenching. ,, Furthermore, the 3+ charge state is easily achieved since RE are preferentially on the isovalent Ga site . The large values for both thermal conductivity and breakdown fields provide further benefits for high temperature and high power electronic devices …”
Section: Introductionmentioning
confidence: 99%